Report of the Joint Committee of the Senate and House of Delegates, appointed to examine the Bank of Virginia and Farmers Bank of Virginia : with bank statements (House document (Virginia. General Assembly. House of Delegates), 1836)
1836 Report of the Joint Committee to examine the various banks, with included bank statements. The report reviewed the Bank of Virginia, Farmers Bank of Virginia, and the Bank of the Valley, and their branches; all were found to be in sound fiscal shape. Of note, the report also indicated that North-western bank was in good condition; however no financial statements were included in this document.